What We Do while Waiting: The Experience of Vulnerability in Trusting Relationships - Ballinger, Gary A.; Schoorman, F. David; Sharma, Kinshuk (Academy of Management Review, 2025)
We explore changes in the emotions of hope and fear in the time between a decision to take a risk based on trust and the time at which that trust is validated or betrayed. We term this period the vulnerability phase and propose that relationships comprise many of these. Blending motivation theories on self-regulation and goal-related behavior, we propose a view of trustors as information processors throughout a vulnerability phase. Trustors evaluate new information on the ability, benevolence, and integrity of the trustee, and their reactions to the implications of these data for goal progress drives changing levels of hope and fear in the phase. These reactions are moderated by the trustor’s perception of how important the resources are to reaching their goals, their regulatory focus, and the strength of the relationship at the time the new information is received. We also discuss the unique role of time in driving levels of fear. We propose that significant changes in these emotions trigger the trustor to engage in a self-focused approach, or avoidance behaviors such as monitoring, looking for alternate partners, and curiosity-based inquiry aimed at preserving progress toward goals that may prematurely bring a vulnerability phase to an end.